Efficacy and safety of frontline rituximab, cyclophosphamide, doxorubicin and prednisone plus bortezomib (VR-CAP) or vincristine (R-CHOP) in a subset of newly diagnosed mantle cell lymphoma patients medically eligible for transplantation in the randomized, phase 3 LYM-3002 study - Drach, Johannes; Huang, Huiqiang; Samoilova, Olga; Belch, Andrew; Farber, Charles; Bosly, André; Novak, Jan; Zaucha, Jan; Dascalescu, Angela; Bunworasate, Udomsak; Masliak, Zvenyslava; Vilchevskaya, Kateryna; et al. (Leukemia & lymphoma, 2018)
This post-hoc subanalysis of the LYM-3002 phase 3 study assessed the efficacy and safety of substituting vincristine in rituximab, cyclophosphamide, doxorubicin and prednisone (R-CHOP; n = 42) for bortezomib (VR-CAP; n = 38) in a subgroup of 80 mantle cell lymphoma (MCL) patients aged <60 years who did not receive stem cell transplantation (SCT) despite medical eligibility. Complete response (CR)/unconfirmed CR (CRu) rates were 67 vs. 39% (odds ratio 3.69 [95% CI(confidence interval): 1.31, 10.41]; p = .012). After 40 months median follow-up, median progression-free survival by independent radiology committee with VR-CAP vs. R-CHOP was 32.6 vs. 12.0 months (hazard ratio (HR) 0.59 [95% CI: 0.31, 1.13]; p = .108); median overall survival was not reached vs. 47.3 months (HR 0.81 [95% CI: 0.33, 1.96]; p = .634). Adverse events included neutropenia (92/76%), thrombocytopenia (70/10%) and leukopenia (65/50%). VR-CAP represents a potential alternative to R-CHOP in combined and/or alternating regimens for younger, SCT-eligible MCL patients.
Keywords: směrnice pro lékařskou praxi jako téma; Doxorubicin; neutropenie; Practice Guidelines as Topic; Thrombocytopenia; transplantace kmenových buněk; cyklofosfamid; prednison; Neutropenia; doba přežití bez progrese choroby; výsledek terapie; myší monoklonální protilátky; Bortezomib; Middle Aged; mužské pohlaví; Adult; Vincristine; Follow-Up Studies; věkové faktory; následné studie; Lymphoma, Mantle-Cell; Rituximab; doxorubicin; ženské pohlaví; leukopenie; bortezomib; Cyclophosphamide; Humans; phase 3; Prednisone; Stem Cell Transplantation; Antibodies, Monoclonal, Murine-Derived; Progression-Free Survival; frontline; rituximab; lidé středního věku; trombocytopenie; vinkristin; Antineoplastic Combined Chemotherapy Protocols; Age Factors; protokoly protinádorové kombinované chemoterapie; dospělí; Leukopenia; Female; mantle cell lymphoma; Treatment Outcome; lidé; Male; lymfom z plášťových buněk